Berberidaceae endémicas del Perú - Ulloa Ulloa, Carmen (2006)
The Berberidaceae are represented in Peru by 32 species in the genus Berberis (Brako & Zarucchi, 1993), most of them shrubs. Most of the 14 endemic species grow in the Mesoandean region, between 2000 and 4200 m elevation. Two of these endemic species have been reported in the Peruvian System of Protected Natural Areas.